Juvenile systemic scleroderma and ecology (literature review and author's research) - V.Ya. Mikuksts; O.V. Syniachenko; O.Е. Chernyshova (Zaslavsky O.Yu., 2017)
The paper deals with a literature review and the results of author's research of ecology role in juvenile systemic sclerosis (SSc). The development of SSc and the rate of its progression in children is closely linked to the adverse environmental factors, in particular, to the degree of contamination of inorganic and organic compounds - pollutants in the atmosphere (heavy metals, carbon monoxide, nitrates, quartz and other industrial products), which increase matrix metalloproteinase activity, induce synthesis of proinflammatory cytokines and autoantibodies, modify vascular endothelial function and production of chemoattractant proteins, collagens, fibronectin and connective tissue biopolymers, thereby enhancing the fibrosing processes. In the Eastern Ukraine the prevalence of juvenile SSc depends on carbon dioxide levels, 3,4-benzopyrene and phenol in the inspired air, and lead and lithium in drinking water, which primarily impacts lungs, heart and musculoskeletal system diseases.